2017
DOI: 10.1038/s41598-017-01206-4
|View full text |Cite
|
Sign up to set email alerts
|

Pentamethylquercetin induces adipose browning and exerts beneficial effects in 3T3-L1 adipocytes and high-fat diet-fed mice

Abstract: Browning white adipocytes may be a new target in anti-obesity therapy. Pentamethylquercetin (PMQ) has been shown to have anti-obesity effects in monosodium glutamate-induced obese mice. Here, we aimed to study the anti-obesity effects of PMQ in vitro and in vivo and to determine if adipose browning is involved in the mechanism underlying the anti-obesity effects of PMQ. We evaluated the effects of PMQ on cell proliferation, cell differentiation, glucose consumption, cellular lipid metabolism, and related brown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…In agreement, Ahmadian et al suggested that ATGL hydrolase activity within adipocytes may lead to UCP1 expression promoting adipose tissue browning [ 62 ]. UCP1, in fact, represents the hallmark of brown adipose tissue (BAT) and is a reliable marker of browning of white adipose tissue (WAT), which has been shown to protect from obesity and type 2 diabetes [ 63 ]. In accordance with our results, it has been reported that a natural flavonoid protects from altered adipogenesis and obesity by inducing browning of WAT [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement, Ahmadian et al suggested that ATGL hydrolase activity within adipocytes may lead to UCP1 expression promoting adipose tissue browning [ 62 ]. UCP1, in fact, represents the hallmark of brown adipose tissue (BAT) and is a reliable marker of browning of white adipose tissue (WAT), which has been shown to protect from obesity and type 2 diabetes [ 63 ]. In accordance with our results, it has been reported that a natural flavonoid protects from altered adipogenesis and obesity by inducing browning of WAT [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…UCP1, in fact, represents the hallmark of brown adipose tissue (BAT) and is a reliable marker of browning of white adipose tissue (WAT), which has been shown to protect from obesity and type 2 diabetes [ 63 ]. In accordance with our results, it has been reported that a natural flavonoid protects from altered adipogenesis and obesity by inducing browning of WAT [ 63 ]. Thus, our data suggest that the proposed antiadipogenic effect of TR may be mediated by activation of the AMPK-ATGL-UCP1 pathway, leading to browning of WAT.…”
Section: Discussionmentioning
confidence: 99%
“…After OGTT, animals in each group continued to live in their corresponding conditions as aforementioned until week 24. Body weight, body length, waistline and food/water consumption were monitored weekly, whilst Lee index (17) was calculated [(body weight) 1/3 /body length] at the end of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that resveratrol can reduce lipogenesis, improve the rate of lipolysis, increase the expression of both PGC-1α protein and UCP1 protein, and promote the browning of WAT by activating the SIRT1 signalling pathway in adipose tissue [ 151 ]. Pentamethylquercetin can heighten mitochondrial biogenesis and upregulate UCP-1 expression in WAT of high-fat-diet fed mice, and it contributes to promoting the browning of WAT [ 152 ]. Curcumin has been shown to enhance the expression of β 3 -adrenergic receptor gene in subcutaneous WAT of mice, thereby increasing plasma levels of noradrenaline and thermogenesis [ 153 ].…”
Section: Current Status Of Research On Browning Agents For the Treatmmentioning
confidence: 99%